Analisis Kelayakan Finansial pada Usaha Ayam Geprek di Kota Batam - Asmarawati, Citra Indah; Ginting, Kristanto (Fakultas Teknik UMRI, 2024)
Batam City offers attractive investment opportunities with optimistic economic growth projections of up to 7.08% in 2024, driven by key sectors such as industry, construction, trade and tourism, supported by infrastructure and government pro-business policies. Changes in people's lifestyles, including the demand for culinary variety, have created opportunities for fast food businesses, especially the popular fried chicken. Culinary tourism in SP Batam attracts tourists. Financial analysis shows that investment in the Ayam Geprek Sambal Lesung Paradisa MSME is feasible and profitable, with an internal rate of return of 9.5%, a 7 month Payback Period, and a multi-product Break Even Point, indicating an attractive business opportunity for entrepreneurs